Analisis Partisipasi Publik yang Bermakna dalam Pembentukan Rancangan Undang-Undang Tentara Nasional Indonesia - Igor Tanjung (Jurnal Hukum Lex Generalis, 2025)
Public participation is a vital element in a democratic rule of law as it ensures the involvement of society in the legislative process. In the Indonesian legal system, this principle is regulated under Law No. 12 of 2011 on the Formation of Legislation as amended by Law No. 13 of 2022, which grants the public the right to provide input, either orally or in writing, at every stage of lawmaking. The Constitutional Court, through Decision No. 91/PUU-XVIII/2020, emphasized that meaningful public participation must be carried out from the planning stage, be open and inclusive, and ensure that every public input is substantively considered. In the context of the Draft Law on the Indonesian National Armed Forces (RUU TNI), various perspectives have emerged regarding the extent to which these principles are truly implemented, particularly with respect to transparency and civil society involvement. This situation raises important juridical and sociological considerations regarding the benchmarks of meaningful participation as well as its implications for the validity of legislation and its acceptance within society.